Language development problems of the deaf children in the primary level - Inton, Carolina N. 1931- (University of the Philippines Diliman, 1967)
This paper is a literature research on the information that teachers and parents of the deaf should know. It investigates the language development problems of deaf children to serve as a basis for improvement of instruction in Speech and Language.